Dmitry Ivanovich Mendeleev - Creator of the Periodic System of Chemical Elements - Semenov I. V. (Fall School Marathon, 2019)
The author of the article addresses significant milestones in the life path of Dmitry Ivanovich Mendeleev, gives the statement of the historian of science, academician B.M. Kedrova, characterizing the personality of the creator of the Periodic system of chemical elements.
Keywords: Менделеева; периодическая система химических элементов; biography; Mendeleev DI; Periodic Table of the Chemical Elements; биография Д; периодическая система